IBM WebSphere V5.0 security - Kovari, Peter (WebSphere handbook series., 2002)
This IBM Redbook provides IT Architects, IT Specialists, application designers, application developers, application assemblers, application deployers and consultants with information necessary to design, develop and deploy secure e-business applications using WebSphere Application Server V5. Part 1, WebSphere security provides a detailed overview of WebSphere Application Server V5 Security. It starts with J2EE security, then goes into details about the modules and components of a J2EE enterprise application; it also covers programmatic security techniques. The last chapter in this part shows all the security-related administrative items in WebSphere Application Server V5. Part 2, End-to-end security offers details about end-to-end security solutions where WebSphere Application Server V5 is part of an enterprise solution. You will find an introduction to Patterns for e-business, in which security is in focus. A very important chapter in this part will discuss the integration between WebSphere Application Server V5 and Tivoli Access Manager. Finally, the Appendixes provide additional information related to chapters in the previous two parts and also describe the sample application available with the book.